MAIT Cells in COVID-19: Heroes, Villains, or Both? - Haeryfar, S M Mansour (Critical reviews in immunology, 2020)
Mucosa-associated invariant T cells (MAIT cells) are unconventional, innate-like T lymphocytes with remarkable effector and immunoregulatory functions. They are abundant in the human peripheral blood and also enriched in mucosal layers and in the lungs, SARS-CoV-2's main ports of entry. Once activated, MAIT cells produce inflammatory cytokines and cytolytic effector molecules quickly and copiously. MAIT cells are best known for their antibacterial and antifungal properties. However, they are also activated during viral infections, typically in a cytokine-dependent manner, which may promote antiviral immunity. On the other hand, it is plausible to assume active roles for MAIT cells in infection-provoked cytokine storms and tissue damage. SARS-CoV-2 infection may be asymptomatic, mild, severe, or even fatal, depending on sex, age, the presence of preexisting morbidities, and the individual's immunological competence, or lack thereof, among other factors. Based on the available literature, I propose that MAIT cells regulate the host response to SARS-CoV-2 and constitute attractive targets in the prevention or clinical management of coronavirus disease 19 (COVID-19) and some of its complications. Unlike mainstream T cells, MAIT cells are restricted by a monomorphic antigen-presenting molecule called MHC-related protein 1 (MR1). Therefore, MR1 ligands should modify MAIT cell functions relatively uniformly in genetically diverse subjects and may be tested as immunotherapeutic agents or vaccine adjuvants in future studies.